First multicentre experience of SABR for lymph node and liver oligometastatic disease on the unity MR-Linac. (June 2022) - Janssen, Tomas M.; Aitken, Katharine; Alongi, Filippo; Barry, Aisling; Bernchou, Uffe; Boeke, Simon; Hall, William A.; Hosni, Ali; Kroon, Petra.S.; Nachbar, Marcel; Saeed, Hina; Jürgenliemk-Schulz, Ina M.; et al.
Highlights: Since August 2018 patients are treated on a 1.5 Tesla MR-Linac (MRL) for oligometastatic disease. We present current workflows and practice standards from seven institutions for the initial patients treated for lymph node and liver metastases. In this work a large variation in treatment strategies was found. Since currently there is little evidence preferring one strategy over the other, clinical registries and future research need to focus on the clinical relevance of the variations in institutional treatment strategies. Abstract: Summary: The treatment of oligometastatic disease using MR guidance is an evolving field. Since August 2018 patients are treated on a 1.5 Tesla MR-Linac (MRL). We present current workflows and practice standards from seven institutions for the initial patients treated for lymph node and liver metastases.